Analisis Tantangan dan Strategi Kereta Api Barang untuk Meningkatkan Daya Saing - Nurhaliza, Syifa; Sukrawan, Yusep (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Freight rail is one mode of transportation that has a large carrying capacity, making it an ideal choice for transporting massive amounts of goods. However, based on data from the FGD: Portrait of Freight Transportation in Indonesia presented by Djoko Setijowarno on March 15, 2023 at Alila Hotel - Solo, the use of freight trains in Indonesia is still very low, which is only 47.6 million tons/year or 0.26% of the total national freight transportation. This research uses the Systematic Literature Review method to analyze the potential and challenges of freight trains. The results show that freight trains have great potential to become the main choice for businesses in distributing their products economically and on time. In addition, the use of freight trains can also provide benefits to the government, including reducing air pollution, road damage due to ODOL (Over Dimension Over Loading) trucks, waste of subsidized fuel oil (BBM), and the high number of road accidents. Therefore, a joint effort is needed from the government, business actors, and the community to increase the use of freight trains as an efficient, economical, and environmentally friendly mode of transportation.